Heart Transplantation in Mustard Patients Bridged With Continuous Flow Systemic Ventricular Assist Device - A Case Report and Review of Literature - Bou Chaaya, Rody G.; Simon, Joel W.; Turrentine, Mark; Herrmann, Jeremy L.; Kay, William Aaron; Guglin, Maya; Saleem, Kashif; Rao, Roopa A. (Frontiers in Cardiovascular Medicine, 2021)
A 34-year-old male with a history of D-transposition of the great arteries (D-TGA) who underwent a Mustard operation at 14 months of age presented in cardiogenic shock secondary to severe systemic right ventricular failure. Catheterization revealed significantly increased pulmonary pressures. Due to the patient’s inotrope dependence and prohibitive pulmonary hypertension, he underwent implantation of a HeartWare HVAD® for systemic RV support. Within 4 months of continuous-flow ventricular assist device (VAD) implantation, complete normalization of pulmonary vascular resistance (PVR) was achieved. He ultimately underwent orthotopic heart transplantation with favorable outcomes. This is the second report of complete normalization of PVR following VAD implantation into a systemic RV in less than 4 months. We conducted a thorough literature review to identify Mustard patients that received systemic RV VAD as a bridge to successful heart transplantation. In this article, we summarize the outcomes and focus on pulmonary hypertension reversibility following VAD implant.